(untitled) (Research, Society and Development, 2021)
With the advances of the COVID-19 pandemic in 2020 and continuing in 2021, there were major impacts on corporate education within hospital health services. Thus, there was a great need to acquire new tools for hospital teaching by health professionals. Therefore, the objective was to seek new changes implemented in the teaching process by corporate education through an integrative review, whose data were collected by the Scielo, Pub Med and VHL database in 2020, with the following descriptors: Continuing Education; Health education; COVID-19; Hospital Education Service. The data were analyzed using Content Analysis. 24 articles were found on the theme with inclusion and exclusion process, with only 11 articles included. Thus, studies show and evidence that there were major impacts for everyone involved in health care directly or indirectly for those who work in a hospital unit, reflecting both for professionals and for patients who meet with COVID-19. Health professionals have to adapt and re-adapt, through coping with new practices of assistance thus inserted, as well as in education and in the development of new methods for training, taking into account restrictions in agglomerations. It was found in the general analysis of this study that, there is a predominantly positive evaluation in the assistance of health professionals, prioritizing customer safety in the COVID-19 contamination process. It should be noted that corporate education has acted heavily in training to minimize the health impacts of employees in hospital care.